2021
DOI: 10.1007/s00360-021-01393-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of AMPK-mTOR-signal pathways and lipid metabolism in response to low- and high-level rapeseed meal diet in Chinese perch (Siniperca chuatsi)

Abstract: It is well known that carnivorous fish cannot use plant-proteins efficiently. They affect lipid metabolism of fish and cause serious problems to fish health. The reasons for this deficiency of fish metabolism are not known well. Chinese perch, a carnivorous fish, can accept artificial diet after domestication and is also considered as a novel model of fish for nutrition studies. Therefore, the aim of this study was to explore the effect of fish meal replacement by low-or high-rapeseed meal on lipid and glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…However, for lipid metabolism, less than 60% of the CSM replacement did not alter the mRNA expression levels of FAS, AGPAT3 and SREBP1. A similar observation could be found in the study of soy bean protein for cod Gadus morhua [ 59 ] and rapeseed meal diet for Chinese perch Siniperca chuatsi [ 60 ]. Furthermore, our recent study on largemouth bass ( Micropterus salmoides ) also presented that the glucose metabolism was more sensitive to feed compositions [ 61 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, for lipid metabolism, less than 60% of the CSM replacement did not alter the mRNA expression levels of FAS, AGPAT3 and SREBP1. A similar observation could be found in the study of soy bean protein for cod Gadus morhua [ 59 ] and rapeseed meal diet for Chinese perch Siniperca chuatsi [ 60 ]. Furthermore, our recent study on largemouth bass ( Micropterus salmoides ) also presented that the glucose metabolism was more sensitive to feed compositions [ 61 ].…”
Section: Discussionsupporting
confidence: 84%
“…LEP in poultry can regulate lipid metabolism in the organism by exciting the sympathetic nervous system ( 46 , 47 ). Li et al ( 48 ) found that LEP could inhibit lipid synthesis in hepatocytes, promote hepatocyte lipolysis and lipid deposition in Siniperca chuatsi under a high-fat feeding environment; Lin et al ( 49 ) found that LEP could improve insulin resistance and increase insulin sensitivity in rats, and Steinberg Greg and Dyck ( 50 ) found that the LEP content decrease accelerated the lipid metabolism in obese rats caused by high-fat diets. In this study, except for HLG50, the LEP contents in the treated groups were significantly decreased, indicating that the hydroxylated lecithin and soy lecithin can reduce LEP content to promote lipid metabolism, making the goslings produce foraging behavior, which was consistent with the above study results.…”
Section: Discussionmentioning
confidence: 99%